ATHUS: um framework para desenvolvimento de jogos para TV Digital Brasileira - Segundo, Ricardo M. C.; Tavares, Tatiana Aires (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2010)
The games are ancient tools of entertainment for humans, but also serving as a tool for your intellectual growth. The games are also a way to overcome our limits, since they essentially have the character of a challenge. A game should give the player the ability to solve problems generated by the dynamics of the game. Thus we have a simple definition of play: the game is an activity of problem solving that provides fun. Due to its large capacity for games, it is important to explore the capabilities of games for the DTV, for that we present a propose of a framework for developing games that aims to facilitate the development of games for the Ginga, and other studies on games for DTV.